2016
DOI: 10.1186/s12940-016-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes among 2- to 3-year-old children in Bangladesh with elevated blood lead and exposure to arsenic and manganese in drinking water

Abstract: BackgroundThe people of Bangladesh are currently exposed to high concentrations of arsenic and manganese in drinking water, as well as elevated lead in many regions. The objective of this study was to investigate associations between environmental exposure to these contaminants and neurodevelopmental outcomes among Bangladeshi children.MethodsWe evaluated data from 524 children, members of an ongoing prospective birth cohort established to study the effects of prenatal and early childhood arsenic exposure in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 34 publications
3
78
1
Order By: Relevance
“…Details of the recruitment strategy, eligibility criteria, and sample collection from children participating in this study have been published previously [24, 25]. Briefly, participants were members of a longitudinal birth cohort established in rural Bangladesh to study the health effects of prenatal and early childhood exposures to metals in the environment.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the recruitment strategy, eligibility criteria, and sample collection from children participating in this study have been published previously [24, 25]. Briefly, participants were members of a longitudinal birth cohort established in rural Bangladesh to study the health effects of prenatal and early childhood exposures to metals in the environment.…”
Section: Methodsmentioning
confidence: 99%
“…When models were adjusted for covariates, sex-stratified analysis showed a statistically significant positive relationship between hair Mn and receptive language scores among males. In Bangladesh, a study examined water Mn concentrations and BSID scores among 524 20–40 month old children [73]. No statistically significant association was observed with cognition in models that also included other neurotoxicants, such as Pb and As.…”
Section: Early Life Exposure To Manganese and Cognitive Outcomesmentioning
confidence: 99%
“…In zebrafish embryos, ~1mM (75 ppm) arsenic has been associated with hypoactivity at 24 hpf and altered neural function with arsenic exposure has been observed [61]. A significant decline in motor function, cognition, and intellectual function has been found in children in Bangladesh who are exposed to arsenic at concentrations similar to those used here in their drinking water [6669]. It has also been shown that zinc can protect neuronal cells grown in culture from arsenic induced cell death [70].…”
Section: Discussionmentioning
confidence: 99%